Strategi Komunikasi Untuk Mensosialisasikan Program Harmonisasi Kebijakan di BRI - Amrina, Afrilla; Naryoso, Agus; Ratri Rahmiaji, Lintang (Interaksi Online, 2024)
Policies implemented without proper governance and communication strategies often lead to misunderstandings or miscommunications. PT Bank Rakyat Indonesia (Persero) Tbk. has implemented a policy harmonization program aimed at aligning its various policies. This study 1 investigates the internal communication strategy employed by BRI to socialize this program, using the Cultip Center Communication Planning Model as a framework. A qualitative descriptive research method was used, with in-depth interviews as the primary data collection technique. Findings reveal that BRI's policy harmonization program was implemented through four key stages: fact-finding, planning, communicating, and evaluating.